Recognizing elderly women with sleep problems and falls from information on comorbidites and medications in a continuous use - Kokić, Ivana; Martinek, Vjenceslav; Bekić, Sanja; Volarić, Mile; Trtica, Ljiljana Majnarić (Advances in Social Sciences Research Journal, 2019)
Geriatric syndromes represent new, comprehensive concepts, which can help identifying vulnerable elderly people with multimorbidity. There is also a problem in using the result in a general practice working environment. We suggest fast audit as a method for conducting research on a small scale. The aim of this study was to find out the specific characteristics that can be used for a fast recognition of elderly women who have sleep problems and are susceptible to falls. We conducted a survey on a sample of 105 elderly women (age range 60-80 years, average 68.7±5.1 SD), in a general practice setting, in the town of Osijek, eastern Croatia. The sleep disturbance was identified using the standard Pittsburgh Sleep Quality Index, while information on falls were taken from electronic health records (eHRs) and patient interviews. We used a multi-item questionnaire for socio-demographic characteristics and lifestyle habits. EHRs were used to diagnose problems associated with sleep disturbances and falls, as well as for the use of medication that affect mental functions. We found out that 74.2% of examined women had sleep problems, and 25.7% of them experienced falls in the past two years. Diagnoses that distinguished women with and those without sleep problems included dyspepsia and urinary tract infections (50% vs. 23.1%). Women with sleep problems, compared to those without them, more commonly used two or more medications, usually antidepressants, analgesics and anxiolytics. Lower back pain and osteoporosis were used as screening tools for women susceptible to falls, compared to women without reports of falling. (81.5% vs 61.5% and 22.2% vs. 5.1%). Women with falls had a higher degree of overlapping with sleep disorders (81.5%). Anxiolytics application could be a link between sleep disorders and falls (the overlapping ratio 68%).